2023
DOI: 10.1097/jxx.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Competency-based evaluation: Collaboration and consistency from academia to practice

Abstract: Competency-based evaluation is not a new concept in nursing education. The Essentials: Core Competencies for Professional Nursing Education (AACN Essentials), published in 2021, and the NONPF Nurse practitioner Role Core Competencies (2022) have provided us with the most recent roadmap for curriculum development and student evaluation. Using these two national guidelines and the Standards for Quality Nurse practitioner Education (2022), we examined ways to unify curriculum and competency in clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…12 The scenario creates a profession. [35][36][37] In a descriptive study that spans over 6 years, involving more than 1000 professionals in various fields, the researchers found that one of the main motivators for professionals to pursue certification is 'career growth' . 38 The lack of an available framework may contribute to the uncertainty of career growth prospects and advancement, especially for the younger generation of practitioners in the field.…”
Section: Registrationmentioning
confidence: 99%
“…12 The scenario creates a profession. [35][36][37] In a descriptive study that spans over 6 years, involving more than 1000 professionals in various fields, the researchers found that one of the main motivators for professionals to pursue certification is 'career growth' . 38 The lack of an available framework may contribute to the uncertainty of career growth prospects and advancement, especially for the younger generation of practitioners in the field.…”
Section: Registrationmentioning
confidence: 99%